CULTURAL IDENTITY AND ISLAMIC MODERATION IN CENTRAL JAVA'S UNIVERSITIES - Kanafi, Imam; Sumeet, Mustafa Hamed Hasan Bin; Mujahid, Imam; N, Irfan A; Bakhri, Syamsul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Radicalism in universities has transformed into covert movements that do not overtly display religious symbols and utilize technology to infiltrate academic communities. This study aims to identify how radical groups adapt within university environments in Central Java, and analyze campus policies’ and extra-campus organizations’ role in promoting religious moderation. It employs a qualitative method and phenomenological approach, collecting data through in-depth interviews, participant observation, and document analysis. It is based on cultural identity theory to understand how the academic community’s religious identities are shaped in response to radical infiltration. The findings reveal that universities in Central Java established Islamic traditions and facilities, including religious moderation centers, moderation gardens, and multifaith worship spaces to resist radical groups, teaching interfaith tolerance to the academic community. Extra-campus organizations are essential for shaping attitudes toward tolerance and religious moderation, depending on the dominant organizations’ nature at each institution. However, Salafi Jihadi, Ikhwanul Muslimin, Hizb ut-Tahrir Indonesia (HTI), Jamaah Islamiyah (JI), Takfiri groups, and ISIS are radical movements, infiltrating extra-campus Islamic organizations. Universities implemented strict policies and preventive measures to combat radicalism within their academic environments. This study provides a deeper understanding of the campus’ strategies and highlights extracurricular organizations’ role in promoting religious moderation.